Direct Aortic Evolut R Implantation as Valve-In-Valve in a Patient Affected by Leriche Syndrome - Dahdah, Pierre; Bruschi, Giuseppe; Jebara, Victor (Journal of Cardiovascular Medicine and Cardiology, 2016)
Transcatheter aortic valve implantation (TAVI) has been designed to treat elderly patients with severe aortic stenosis considered high-risk surgical candidates. Due to the large device size, even of current generation systems, the trans-femoral approach requires favorable ilio-femoral arterial anatomy; this approach is contraindicated in patients with excessive atherosclerosis, calcifications, or tortuosity of ilio-femoral arteries. We report the case of a 75-year-old female affected by Leriche syndrome who successfully underwent direct aortic (DAo) transcatheter aortic valve implantation with a Medtronic CoreValve Evolut R (Medtronic Inc., Minneapolis, MN, USA) as valve-in-valve implantation to treat a degenerate aortic bioprosthesis.